Web applications in learning process: a comparison between quantity surveying and information technology undergraduates - Tan, Chin Keng; Yeoh, Kah Ching (2014)
The use of web applications has become a trend in many disciplines including education. In view of the influence of web application in education, this study examines web application technologies that could enhance undergraduates’ learning experiences, with focus on Quantity Surveying (QS) and Information Technology (IT) undergraduates. The objectives of the study are to: 1. Determine the level of usage of educational related web applications by QS undergraduates and IT undergraduates. 2. Determine is there any statistically significant difference in the use of educational related web applications by QS undergraduates compare to IT undergraduates. The data for this survey were collected from 130 QS undergraduates and 42 IT undergraduates from two higher education institutions in Malaysia. Descriptive statistics are used to determine the level of usage of each web application among the two groups of students. The value of median is determined to measure the central tendency of each variable as the data is of ordinal level in measurement. The findings of the study indicate that: 1. Generally, undergraduates of both QS and IT are exposed to web applications. However, they are more familiar with certain applications (e.g. Social Networking, Web Search, etc.) but unfamiliar with other applications (e.g. Online Portfolio, Podcast, etc.). 2. The usage of web applications by QS undergraduates are on par with IT undergraduates although there are certain differences on the pattern of usage observed. 3. The differences of the web application usage pattern can be explained by the differences of the nature of the studies of both disciplines, in which QS undergraduates are required more in searching for data through the web whereas IT undergraduates are required to use the web applications to development IT systems.